(3GdGfJUGQ deG LQO aj GdePgH ef GdCNHGQ hGdGNJjGQs - (3YHO Gddg GHf eMeO Hf gHg Gddg GHf GdeWgQ Hf CHi YUQhf GdehUdj GdTGaYj, TQa GdOjf, CHh SYjO, J (B585 (3g` s
(3ChdgG (B:s
(3Ghd GdcJGH s
(3BNQgG (B:s
(3BNQ HGH GdUjO hGdPHGFM s
(3HChdg (B40 (3hQbI cJHJ ai GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B11 - (3U (B287 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(1102) s
Keywords: (3Gdabg GdTGaYjs